EFFECT OF CERTAIN INSECTICIDES ON SURVIVAL OF TOBACCO CUTWORM, Spodoptera litura Fabricus (Lepidoptera: Noctuidae) - MAHAJAN, KAPILA; JASKARAN, .; SINGH, AMANDEEP; THAKUR, ABHINAY; SINGH, RANDEEP (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
The bio-efficacy of four insecticides viz. indoxacarb 14.5SL, fenvalerate 20EC, quinalphos 25EC and imidacloprid 17.8SL was tested against Spodoptera litura (Fab.) (Lepidoptera: Noctuidae) by artificial diet, leaf dip and topical treatment methods. Third instar larvae of F1 generation of field population artificially reared in laboratory were deployed in bio-assays. The mortality data was recorded at 24, 48 and 72 hours after exposure of these larvae at three different concentrations viz. 0.05%, 0.1% and 0.2%. The susceptibility data obtained during the investigation indicated that the 3rd instar larvae were highly susceptible to Indoxacarb causing 100% mortality even at lowest concentration. The quinalphos and fenvalerate were similar in toxicity leading to 50% mortality at higher concentration. The order of toxicity was indoxacarb> quinalphos> fenvalerate> imidacloprid. Indoxacarb is an oxadiazine insecticide that works as a sodium channel blocker and reported to have a good field activity against a number of lepidopteran pests.